2021
DOI: 10.1007/s40858-021-00433-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inter and intra anastomosis group of Rhizoctonia spp. isolated from different crops in Peninsular Malaysia

Abstract: Rhizoctonia is a widespread soilborne fungus in different agroecosystems worldwide. It has been reported as a destructive fungal pathogen that caused various types of diseases on a wide variety of crops. The aim of this study was to characterize Rhizoctonia spp. isolated from various crops. We obtained 37 Rhizoctonia isolates from rice, corn, spinach, chrysanthemum, and chili grown in various locations in Peninsular Malaysia. A total of 35 isolates were classified under Rhizoctonia solani (multinucleate) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Other factors such as spontaneous natural mutations, genetic drift, gene flow, crop rotation, sampling year, and alternate host might have played significant role in terms of variation among the isolates of C. falcatum [70,[75][76][77][78]. Furthermore, molecular markers are more informative than rDNA-ITS sequencing in terms of detecting the diversity within the individual population but less successful in detecting the variation between different populations [79].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as spontaneous natural mutations, genetic drift, gene flow, crop rotation, sampling year, and alternate host might have played significant role in terms of variation among the isolates of C. falcatum [70,[75][76][77][78]. Furthermore, molecular markers are more informative than rDNA-ITS sequencing in terms of detecting the diversity within the individual population but less successful in detecting the variation between different populations [79].…”
Section: Discussionmentioning
confidence: 99%
“…They stated that the criteria of the geographical area could be examined and mentioned the role of the anastomosis group in creating more critical diversity. Although other researchers have reported a genetic relationship and geographical location (25,26), its incompatibility can be found in other factors that cause genetic diversity. In this study, at the level of 80% similarity, the number of groups increased to 23 groups, which indicates the very high diversity observed among the isolates.…”
Section: Results Of Cluster Analysismentioning
confidence: 95%
“…botrytis L.), spinach (Spinacea oleracea L.), radish (Raphanus sativus L.) and cabbage (Brassica oleracea L. var. capitata L.) in Malaysia (Rashed et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studies of cross‐pathogenicity of binucleate Rhizoctonia AG‐Fb are needed to identify species and genotypes susceptible to the phytopathogen. For example, an isolate of binucleate Rhizoctonia obtained from spinach was pathogenic to cauliflower, radish and cabbage in Malaysia (Rashed et al., 2021). Additionally, it was observed that isolates of binucleate Rhizoctonia from native pastures also exhibited pathogenicity towards soybean crops (Kodati et al., 2021).…”
Section: Discussionmentioning
confidence: 99%